Torcidas organizadas e sociabilidade juvenil no nordeste. - Santos, Amanda Farias dos (2009)
We studied in this work the sociability of the organized groups of football fans. Our object of study was the Grêmio Recreativo Social e Cultural de Torcida Organizada Comando Alvi Rubro, of the Clube de Regatas Brasil (CRB), rooted in Maceió. We understood, through an approach ethnomethodology, the real meaning of what is to be fan today, using the categories of Sociability, Masculinity, Youth, Identity and Violence. The latter with special attention because the constant controversies involving the fans and conflicts reported by various media. We believe that the sports phenomenon, in the time it takes spaces of sociability and exchange, also offers a field of conflicts that may result in the practice of violence. However, we found that carrying out such violence may be subject, often, to the particularities and uniqueness of group behavior and the way that it identifies and internalises its values and references. This aspect, verified by field research, don't permited us to link directly the violence to the football fans. The processes of Sociação, observed by means of semi-structured interviews with various actors and the participant observation carried out at different times, allowed us to view a range of factors capable of constituting a social group such as organized fans, producing specific practices of a community, providing a number of possibilities to interfere in his work. KEYWORDS: Football Brazil Social aspects Football Northeast Brazil Violence in sports Football fans - Sociability